Direito, saúde e cidadania do idoso em tempos de Covid-19 - Oliveira, Marcelo Brigagão de (2023)
Objectives: the available epidemiological data state that it was the population over 60 years of age that suffered the highest mortality rate among all age groups. Thus, the general objective of the study was: to know the perception of their quality of life and their satisfaction with their health during the pandemic period. Specific objective: To know more deeply what it was like to live in confinement in terms of their psychological health and social relationships. Methodology: Quantitative and qualitative research conducted in a Brazilian city in the State of Minas Gerais (Poços de Caldas) in Brazil, composed of 30 participants (15 institutionalized and 15 non-institutionalized) of both sexes, over 60 years of age and without cognitive deficit. The abbreviated WHO quality of life questionnaire WHOQOL-Bref was applied. Results: The results of the study allowed us to conclude that institutionalized elderly people survived the period of confinement caused by the pandemic more successfully. With higher indices of perception of their quality of life and satisfaction with their general health. The most surprising aspect of this research is that the institutionalized elderly showed greater psychological resilience and preservation of their social relationships, since the fact of being in a community isolated from the outside environment allowed a relationship between them. This was unthinkable for those who lived at home. The latter showed a worse satisfaction with their health and social relationships. Conclusion: long-stay institutions functioned as a protective factor for our elderly.